Twin polymerization at spherical hard templates: An approach to size-adjustable carbon hollow spheres with micro- or mesoporous shells - Boettger-Hiller, Falko; Kempe, Patrick; Cox, Gerhard; Panchenko, Alexander; Janssen, Nicole; Petzold, Albrecht; Thurn-Albrecht, Thomas; Borchardt, Lars; Rose, Marcus; Kaskel, Stefan; Georgi, Colin; Lang, Heinrich; et al. (Angewandte Chemie International Edition, 2013)
Kitset hollow spheres: The combination of twin polymerization with hard templates makes hollow carbon spheres (HCSs) with tailored properties easily accessible. The thickness and pore texture of the HCS shells and also the diameter of the spherical cavity can be varied. The application potential of synthesized HCS is substantiated by an excellent cycling stability of lithium-sulfur batteries. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: hollow carbon spheres; lithium-sulfur battery; porous carbon; twin polymerization